Salinity Resistance of Five Amaranth (Amaranthus cruentus) Cultivars at Young Plants Stage - Wouyou, Agapit; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; ASSOGBA KOMLAN, Françoise; MONTCHO, David; ZANKLAN, Ahissou Séraphin; LUTTS, Stanley; GNANCADJA, ANDRÉ LÉOPOLD SIMPLICE (My University, 2017)
Aims: In this study, salt resistance level of five amaranth (Amaranthus cruentus) cultivars: AA-04-028, AA-04-017, Locale, Rouge and Red-Sudan, was evaluated at young plants stage. Study Design: The experiment was laid out as a Randomized Complete Block Design (RCBD) with four replications. Place and Duration of Study: The experiment was carried out in a screen house at Center ofAgricultural Research of Agonkanmey, Commune of Abomey-Calavi, Republic of Benin from July to September 2016. Methodology: Three weeks old plants of the five cultivars were submitted in pots containing a mixture of potting soil and sand to four NaCl concentrations: 0, 30, 60 and 90 mM NaCl corresponding respectively to an electric conductivity of 0, 1.915, 4.815 and 8.39 dS.m-1 by irrigation every two days. Plant growth parameters were evaluated after two weeks. Results: Salt effect caused a reduction of young plant growth whatever the growth parameter considered with a significant difference among cultivars. The growth reduction due to NaCl is lower and non significant in cultivar Rouge for all growth parameters except root fresh mass, whereas this reduction is higher and significant (p=.05) in cultivars Locale and AA-04-028 for all growth parameters. For cultivars Red-Sudan and AA-04-017, the reduction due to NaCl was significant (p= .05) only for leaf number and plant height. The results indicated that cultivar Rouge was the less affected by NaCl, followed by AA-04-017, Red-Sudan and AA-04-028; cultivar Locale was the most affected. Conclusion: Plant height, leaf number and root length appeared as the most suitable growth parameters for studying salt stress effect in Amaranthus cruentus. For the first time, we demonstrated that there is a variability of relative salt-stress resistance among A. cruentus cultivars at young plant stage. Among the five cultivars, Rouge appeared as the most salt resistant whereas cultivar Locale was the most salt sensitive at young plants stage.
Keywords: Cultivars discrimination; leaf vegetable; NaCl salt-stress; root growth; shoot growth